Metabolic Linkage and Correlations to Storage Capacity in Erythrocytes from Glucose 6-Phosphate Dehydrogenase-Deficient Donors - Reisz, Julie A.; Tzounakas, Vassilis L.; Nemkov, Travis; Voulgaridou, Artemis I.; Papassideri, Issidora S.; Kriebardis, Anastasios G.; D’Alessandro, Angelo; Antonelou, Marianna H. (Frontiers in Medicine, 2018)
Objective In glucose 6-phosphate dehydrogenase (G6PD) deficiency, decreased NADPH regeneration in the pentose phosphate pathway and subnormal levels of reduced glutathione result in insufficient antioxidant defense, increased susceptibility of red blood cells (RBCs) to oxidative stress, and acute hemolysis following exposure to pro-oxidant drugs and infections. Despite the fact that redox disequilibrium is a prominent feature of RBC storage lesion, it has been reported that the G6PD-deficient RBCs store well, at least in respect to energy metabolism, but their overall metabolic phenotypes and molecular linkages to the storability profile are scarcely investigated. Methods We performed UHPLC-MS metabolomics analyses of weekly sampled RBC concentrates from G6PD sufficient and deficient donors, stored in citrate phosphate dextrose/saline adenine glucose mannitol from day 0 to storage day 42, followed by statistical and bioinformatics integration of the data. Results Other than previously reported alterations in glycolysis, metabolomics analyses revealed bioactive lipids, free fatty acids, bile acids, amino acids, and purines as top variables discriminating RBC concentrates for G6PD-deficient donors. Two-way ANOVA showed significant changes in the storage-dependent variation in fumarate, one-carbon, and sulfur metabolism, glutathione homeostasis, and antioxidant defense (including urate) components in G6PD-deficient vs. sufficient donors. The levels of free fatty acids and their oxidized derivatives, as well as those of membrane-associated plasticizers were significantly lower in G6PD-deficient units in comparison to controls. By using the strongest correlations between in vivo and ex vivo metabolic and physiological parameters, consecutively present throughout the storage period, several interactomes were produced that revealed an interesting interplay between redox, energy, and hemolysis variables, which may be further associated with donor-specific differences in the post-transfusion performance of G6PD-deficient RBCs. Conclusion The metabolic phenotypes of G6PD-deficient donors recapitulate the basic storage lesion profile that leads to loss of metabolic linkage and rewiring. Donor-related issues affect the storability of RBCs even in the narrow context of this donor subgroup in a way likely relevant to transfusion medicine.